Rapid Synthesis of Carbon Dots by Hydrothermal Treatment of Lignin - Chen, Wenxin (Materials (Basel), 2016)
A rapid approach has been developed for the fluorescent carbon dots (CDs) by the hydrothermal treatment of lignin in the presence of H(2)O(2). The as-synthesized CDs were found to emit blue photoluminescence with excellent photostability. Moreover, the CDs displayed biocompatibility, low cytotoxicity, and high water solubility properties. Finally, the as-resulted CDs were demonstrated to be excellent probes for bioimaging and biosensing applications.